Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0005975.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolus: Structure and Function

Abstract: The nucleolus is the nuclear subdomain that assembles ribosomal subunits in eukaryotic cells. The nucleolar organiser regions of chromosomes, which contain the genes for pre‐ribosomal ribonucleic acid ( rRNA ), serve as the foundation for nucleolar structure. The nucleolus disassembles at the beginning of mitosis, its components disperse in various parts of the cell and reassembly occurs during telophase and early G1 phase. Ribosome assembly begins with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…These data showed that HLBs not only concentrate essential limited factors for histone pre-mRNA processing but that the absence of HLBs results in specific transcriptional disruption and a small but significant level of spurious polyadenylation of unprocessed histone pre-mRNA. PML NBs and nucleoli have also been suggested to be important for transcriptional activation and repression of physically-associated gene loci, but the exact role of the PML NB in this process is still unclear [39,91]. These studies indicate that the formation of specialized nuclear microenvironments allows cells to produce large quantities of specific RNAs through enrichment of limited but essential protein factors.…”
Section: Cajal Bodies Concentrate Limited Factors To Clear Unprocessementioning
confidence: 99%
“…These data showed that HLBs not only concentrate essential limited factors for histone pre-mRNA processing but that the absence of HLBs results in specific transcriptional disruption and a small but significant level of spurious polyadenylation of unprocessed histone pre-mRNA. PML NBs and nucleoli have also been suggested to be important for transcriptional activation and repression of physically-associated gene loci, but the exact role of the PML NB in this process is still unclear [39,91]. These studies indicate that the formation of specialized nuclear microenvironments allows cells to produce large quantities of specific RNAs through enrichment of limited but essential protein factors.…”
Section: Cajal Bodies Concentrate Limited Factors To Clear Unprocessementioning
confidence: 99%
“…Keeping in mind the multifunctional nature of the nucleolus (Boisvert et al 2007;Hernandez-Verdun et al 2010;Shaw and Brown 2012;Grummt 2010Grummt , 2013Olson and Dundr 2015), we are tempted to assume that the nucleolus breakdown and disappearance at the mid-lampbrush stage oocytes is a sign of the so-called Bnucleolar stress^ (Boulon et al 2010;Grummt 2013;James et al 2014;Olson and Dundr 2015). This stress results in p53 transcription factor stabilization followed by cell growth arrest and ultimately apoptosis (Horký et al 2002;Manfredi 2010;Pederson 2011;Grummt 2013).…”
Section: Nor Activity In Oocytes From Juvenile Birdsmentioning
confidence: 96%
“…One of these sub-compartments is the nuclear lamina; the lamina-associated domains (LADs) are large genomic regions that are generally transcriptionally repressed and are located along the nuclear envelope (Guelen et al 2008). Other nuclear structures that associate with specific loci include the nucleolus (Nemeth and Langst 2011;Olson and Dundr 2001), transcription factories (Osborne et al 2004) and a variety of nuclear bodies, such as promyelocytic leukaemia (PML) nuclear bodies (Ching et al 2013), Cajal bodies (Smith and Lawrence 2000) and histone locus bodies (Liu et al 2006;Nizami et al 2010). This spatial proximity between specific loci and nuclear factors or sub-compartments may be a consequence of either active movement directed by nuclear skeletal elements (Bridger 2011;Bridger et al 2014;Chuang et al 2006;Dundr et al 2007) or may reflect a passive mass action and selfassembly of functional domains that stabilize once formed (reviewed in Chuang and Belmont 2007).…”
Section: Higher Order Chromatin Structure and Organizationmentioning
confidence: 99%